Evaluating Dalvik Instructions through Dynamic Analysis of Bytecodes - Ávila, Kariston Augusto; Wagner, Flávio Rech; Carro, Luigi (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
Android is an operating system for smartphones developed by Google that uses the Dalvik Virtual Machine to ensure compatibility of their applications between platforms that use it. This paper presents the evaluation of Dalvik instructions from the results of dynamic analysis of Dalvik bytecodes. Its objective is the identification of a subgroup of instructions which is responsible for most of the execution time in typical embedded applications. The results show that a few instructions are responsible for most of applications' execution time.